THE IMPACT OF NON-FOOD COMMODITY INFLATION ON CHANGES OF HOUSEHOLD WELFARE IN ACEH PROVINCE - Yasrizal Yasrizal (AFEBI Economic and Finance Review, 2018)
The relations of inflation and poverty can be seen from the contribution commodities of poverty contributor. Increasing prices on the commodity of poverty contributor leads to declining real incomes and income loss in households causing poverty. The commodity of poverty contributor is dominated by fuel and LPG commodities. The AIDS model is a  development of the Engel curve and Marshall equations derived from the theory of satisfaction maximization. This model uses the budget share ofhousehold on a selected commodity to represent demand variables. This study is an empirical study. The data used are primary and secondary data obtained from field research and literature. The study is located in Banda Aceh and Meulaboh. By using an almost ideal model of demand or an AIDS model, it will be seen that household behavior responds to changes in the price of the commodity of poverty contributor. From observation, inflation rate of non food commodity has a big effect on the welfare of Aceh Province community, both for Banda Aceh and Meulaboh households. The on-food commodity inflation has a huge influence to reduce household welfare inMeulaboh.JEL Classification: D10, D11, D12Keywords: AIDS Model, Elasticity, Inflation, Non-food Commodity of PovertyContributor.